(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chemotherapy of malignant neoplasms is the basis of modern oncological practice, but its effectiveness is often limited by toxic complications from the liver and kidneys. These organs play a key role in the metabolism and excretion of antitumor drugs and often become a target for cytotoxic effects. One of the promising areas of organ protection is the use of specialized amino acids with antioxidant, anti-inflammatory and metabolic protective effects.